The Sense of Belonging and Unbelonging in Halide Edip’s Proto-Feminist Works in English - BAŞ, IŞIL (My University, 2019)
Europe is being defined in new ways. On the first hand there is the issue of postsocialist countries in central and eastern Europe. Secondly due to high level of migrations now Europe is more multicultural than ever. Hence any European perspective necessarily involves the recognition of internal gender regimes of countries and cultures that comprise it. It also goes without saying that women's movements are "embedded in particular histories and geographies" hence any gender agenda should take into account the diversities. My paper will concentrate on Turkey's specific place in Europe and our experience in the feminist movement and women's studies both of which are inextricably linked to our sense of belonging and unbelonging to the European culture. To that end I will be analyzing Halide Edip Adivar's works many of which were published in English due to her exile upon the fall off between her and Ataturk, the founder of modern Turkey over her views on authoritarian regimes. Her autobiographies, articles and novels display the sense of belonging and unbelonging of this exceptional woman who was the first graduate of American Academy of girls in Istanbul, the first woman in 1928 to lecture on politics at the Williamstown Political Institute, lecturer at Colombia University, founder of the very first English Language and Literature department in Turkey, writer of the first English Literature survey in 3 volumes as well as being a proto-feminist, nationalist and sergeant during the years of the War of Independence.